2010
DOI: 10.1186/1471-2334-10-247
|View full text |Cite
|
Sign up to set email alerts
|

Potential for airborne transmission of infection in the waiting areas of healthcare premises: stochastic analysis using a Monte Carlo model

Abstract: BackgroundAlthough many infections that are transmissible from person to person are acquired through direct contact between individuals, a minority, notably pulmonary tuberculosis (TB), measles and influenza are known to be spread by the airborne route. Airborne infections pose a particular threat to susceptible individuals whenever they are placed together with the index case in confined spaces. With this in mind, waiting areas of healthcare facilities present a particular challenge, since large numbers of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 20 publications
0
44
1
Order By: Relevance
“…Beggs et al 23 estimated the risks of airborne transmission of TB, influenza, and measles in a hypothetical hospital waiting area containing a single infectious individual and found respective mean risks of infection for susceptible persons of 0.3%, 2.6%, and 13.5% for a 30-minute wait and 0.8%, 6.6%, and 30.9% for a 60-minute wait. Despite differences in methodology, the present study and that of Beggs et al 23 highlight the approximate relative risks faced by individuals during the time spent waiting for and during medical consultations. The risk of an individual acquiring influenza appears more likely during the actual consultation, if the room was previously occupied by an infectious individual, than during the period spent in a waiting room based on the limited scenarios modeled in the 2 studies.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Beggs et al 23 estimated the risks of airborne transmission of TB, influenza, and measles in a hypothetical hospital waiting area containing a single infectious individual and found respective mean risks of infection for susceptible persons of 0.3%, 2.6%, and 13.5% for a 30-minute wait and 0.8%, 6.6%, and 30.9% for a 60-minute wait. Despite differences in methodology, the present study and that of Beggs et al 23 highlight the approximate relative risks faced by individuals during the time spent waiting for and during medical consultations. The risk of an individual acquiring influenza appears more likely during the actual consultation, if the room was previously occupied by an infectious individual, than during the period spent in a waiting room based on the limited scenarios modeled in the 2 studies.…”
Section: Discussionmentioning
confidence: 59%
“…It is important to keep in mind that our risk estimates are expressed as percentages, and although this is a convenient and intuitive metric, it might not translate to a significant absolute number of infections in a room with low occupancy. 19,23 The points at which the existing air exchange rate in the Lung Function Laboratory intersects the curves shown in Figure 1 indicate that increasing air exchange further would provide a negligible reduction to an already very low infection risk. The attendant increase in energy consumption required would be difficult to justify when the size of the room and its typical occupancy of up to 10 persons are considered.…”
Section: Discussionmentioning
confidence: 93%
“…As described in this outbreak, nosocomial transmission can lead to measles in HCWs, other patients at the hospital, and susceptible hospital visitors. Measles is one of the most contagious viral diseases and patients frequently visit hospitals or health care facilities for diagnosis and management, which might lead to nosocomial transmission if appropriate infection control measures are not immediately instituted ( 8 ). …”
Section: Resultsmentioning
confidence: 99%
“…A likely explanation for these findings is the high baseline risk of respiratory infection in children. In a study using a Monte Carlo stochastic model to analyze the transmission of airborne infections in a hospital waiting area under various occupancy levels, waiting times, and ventilation rates, it was found that the mean probability for acquiring influenza, although relatively small, increased with increasing waiting times and decreasing distance among visitors 12 . Emergency departments in Greek hospitals are typically overcrowded during winter and many parents in our study reported that they moved away from symptomatic patients, a fact that may had an impact on the extremely low rate of transmission of infection.…”
Section: Discussionmentioning
confidence: 99%